THU0412 Cardiovascular Outcomes in Patients with Rheumatoid Arthritis, Psoriasis and Psoriatic Arthritis: A Systematic Review and Meta-Analyses. (10th June 2014) - McFarlane, A.; Roubille, C.; Richer, V.; Starnino, T.; McCourt, C.; Fleming, P.; Siu, S.; Kraft, J.; Lynde, C.; Pope, J.; Gulliver, W.; Dutz, J.; et al.
Abstract : Background: Rheumatoid arthritis (RA), psoriasis (PsO) and psoriatic arthritis (PsA) are associated with increased risk of CV-mortality but less clearly related to specific cardiovascular outcomes (CVO.) Objectives: To evaluate important CVO in RA, PsO and PsA patients. Methods: Medline, Embase, Cochrane and abstracts from ACR/EULAR/AAD/EADV were searched for in English language full-length articles and abstracts published up to January 15, 2013 describing CVO in observational studies in RA, PsO and PsA patients. Outcomes included all-cause and CV-mortality, and specific CVO including myocardial infarction (MI)/acute coronary syndrome (ACS), cerebrovascular accident (CVA – including stroke or transient ischemic attack), heart failure (HF) and peripheral artery disease (PAD). Random effects meta-analyses were performed. Results: Out of 3457 references, 127 observational studies (RA=89; PsO=27; PsA=11) were included. Important effect size estimates represented as standardized mortality (SMR) and morbidity (SMoR) ratios are listed in Table 1 . Conclusions: RA, PsO and PsA are associated with several important CVO's including less reported outcomes such as PAD, CVA and HF. These complications may be less recognized by physicians. Fewer studies exist for PsA but CVO's appear increased overall. Risk reduction strategies should be considered. Acknowledgements: Dr. Ben Vandermeer provided invaluable statistical consulation and analysis. Disclosure of Interest: : A. McFarlane Grant/research support: This study was supported by an unrestricted grant from AbbVie., C. Roubille Grant/research support: This study was supported by an unrestricted grant from AbbVie. Fellowship grants/bursary from the Foundation of the University of Montreal Hospital Center (CHUM)., V. Richer Grant/research support: This study was supported by an unrestricted grant from AbbVie., T. Starnino Grant/research support: This study was supported by an unrestricted grant from AbbVie., C. McCourt Grant/research support: This study was supported by an unrestricted grant from AbbVie. Salary for the fellowship in Vancouver was funded by a Fellowship from Janssen-Ortho Canada and the British Association of Dermatology., P. Fleming Grant/research support: This study was supported by an unrestricted grant from AbbVie., S. Siu Grant/research support: This study was supported by an unrestricted grant from AbbVie., J. Kraft Grant/research support: This study was supported by an unrestricted grant from AbbVie. Investigator support from Abbvie, Amgen, Galderma, Janssen, Novartis., Consultant for: Abbvie, Amgen, Galderma, Janssen, Novartis, Leo., Speakers bureau: Abbvie, Amgen, Galderma, Janssen, Leo., C. Lynde Grant/research support: This study was supported by an unrestricted grant from AbbVie. Investigator support: Abbvie, Amgen, Celgene, Janssen-Ortho, Novartis, Eli Lilly, Merck, Leo Pharma., Consultant for: Abbvie, Amgen, Celgene, Janssen-Ortho, Novartis, Eli Lilly, Merck, Leo Pharma., Speakers bureau: Abbvie, Amgen, Celgene, Janssen-Ortho, Novartis, Eli Lilly, Merck, Leo Pharma., J. Pope Grant/research support: This study was supported by an unrestricted grant from AbbVie. Research support from AbbVie, Actelion, Amgen, Astra Zeneca, Bayer, BMS, Celgene, Genentech, GSK, BMS, Jansen & Jansen, MedImmune, Mediquest, Novartis, Pfizer, Roche, United Chemicals Belgium., Consultant for: AbbVie, Actelion, Amgen, Astra Zeneca, Bayer, BMS, Celgene, Genentech, GSK, BMS, Jansen & Jansen, MedImmune, Mediquest, Novartis, Pfizer, Roche, United Chemicals Belgium., W. Gulliver Grant/research support: This study was supported by an unrestricted grant from AbbVie. Research support from Abbott/AbbVie, Actelion, Amgen, Astellas, Bio-K, Celgene, Galderma, Janssen, LEO Pharma, Merck/Schering, Novartis, Pfizer, Roche and Valeant., Consultant for: Abbott/AbbVie, Actelion, Amgen, Astellas, Bio-K, Celgene, Galderma, Janssen, LEO Pharma, Merck/Schering, Novartis, Pfizer, Roche and Valeant., Speakers bureau: Abbott/AbbVie, Actelion, Amgen, Astellas, Bio-K, Celgene, Galderma, Janssen, LEO Pharma, Merck/Schering, Novartis, Pfizer, Roche and Valeant., J. Dutz Grant/research support: This study was supported by an unrestricted grant from AbbVie. Research support Abbvie, Centocor, Janssen- Ortho, Novartis, ONO Pharmaceuticals, Roche, Consultant for: Janssen-Ortho, AbbVie Amgen, Leo, Roche, Speakers bureau: Janssen-Ortho, AbbVie Amgen, Leo, L. Bessette Grant/research support: This study was supported by an unrestricted grant from AbbVie. Research support AbbVie, UCB, Janssen, and Amgen., Consultant for: AbbVie, UCB, Janssen, and Amgen., Speakers bureau: AbbVie, UCB, Janssen, and Amgen., R. Bissonnette Grant/research support: This study was supported by an unrestricted grant from AbbVie. Research grants and honoraria AbbVie, Amgen, Celgene, Eli-Lilly Galderma, Incyte, Janssen, Leo Pharma, Merck, Novartis, Pfizer, Tribute., Consultant for: AbbVie, Amgen, Celgene, Eli-Lilly Galderma, Incyte, Janssen, Leo Pharma, Merck, Novartis, Pfizer, Tribute., B. Haraoui Grant/research support: This study was supported by an unrestricted grant from AbbVie. Grant support from Abbvie, Amgen, BMS, Celgene, Janssen, Pfizer, Roche, UCB., Consultant for: Abbvie, Amgen, BMS, Celgene, Janssen, Pfizer, Roche, UCB., S. Keeling Grant/research support: This study was supported by an unrestricted grant from AbbVie. Unrestricted educational funding received from the following:Pfizer, Janssen, Astrazeneca, Roche., Consultant for: Participated in advisory boards as consultant for:Janssen, AbbVie, Roche, Amgen. DOI: 10.1136/annrheumdis-2014-eular.1348